If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4x + -3 = 6x + -123 Reorder the terms: -3 + -4x = 6x + -123 Reorder the terms: -3 + -4x = -123 + 6x Solving -3 + -4x = -123 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. -3 + -4x + -6x = -123 + 6x + -6x Combine like terms: -4x + -6x = -10x -3 + -10x = -123 + 6x + -6x Combine like terms: 6x + -6x = 0 -3 + -10x = -123 + 0 -3 + -10x = -123 Add '3' to each side of the equation. -3 + 3 + -10x = -123 + 3 Combine like terms: -3 + 3 = 0 0 + -10x = -123 + 3 -10x = -123 + 3 Combine like terms: -123 + 3 = -120 -10x = -120 Divide each side by '-10'. x = 12 Simplifying x = 12
| -0x+10-3x=-5(x-2)+2 | | x+22+3x=-19-3x-22 | | -2x+9-3x=-5(x-2)+2 | | -2x+12-3x=-5(x-2)+0 | | -2x+12-3x=5(x-2)+2 | | 4+3x=7x-24 | | 3(s+2)-(2s-3)=5 | | 3x^2-3x=21 | | 3x+8y+2=0 | | 4x=(-8) | | 5/8*8/5 | | -2x+12-3x=-5(x-2)+3 | | 2x+12-2x=-5(x-2)+2 | | 4x+3y-5=0 | | 8+3x=6x+26 | | -4x+12-2x=-5(x-2)+2 | | x+6-x-4=10-x | | 6x+y=8x-2y | | 4x+2(x+1)=26 | | 12(7X-1)-8(6X+1)+(5X+3)11=23(4X-X)+23 | | -1x+12-3x=-5(x-2)+1 | | 2+3x=5x+24 | | 5/2=17/3 | | 3x+7x=850 | | 0=ln(x^2+5)+0.5x+1 | | -2x+12-2x=-5(x-1)+2 | | -2x+12-2x=-5(x-2)+2 | | 3x+5x=850 | | 12+10=14y-3y | | -2x+10-3x=-5(x-2)+2 | | 8-6x-3=-21+4x-14 | | 7(x+2)=9x+2 |